Problematika Sengketa Tanah di Dati Wasila Ambon - Jihan Usamah Bin Abbas; Ali Maskur (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
Research focuses on dealing with land dispute issues in Dita Wasila Ambon's. Seeking the substance of the matter, the subject of law involved, the position of the dispute case, the court ruling and the follow-up of the execution of the court decision. The research location is at Dati Wasila Ambon. Qualitative methods based on case studies with a concentration on explanators as well as the use of single instruments. File obtained interview sources, observations and supporting documents, analysis techniques and data presentation are performed in a descriptive manner. The results of the research showed that the land dispute in Dati Wasila involved the landowners Wasawoy and Hatala. Mutual lawsuits at the green table from the Ambon State Court, the High Court to the Court of Cassation of the Supreme Court. The problem becomes more complicated when the land execution is carried out because of the many problems and stakeholders on the land; land boundaries that do not match the data, have been done licensing, the process of legalization of land certification. Dispute settlement is not enough with a court ruling alone but requires the involvement of land bodies, local governments, villages, indigenous figures and the public.